Association between right ventricular dysfunction and adverse cardiac events in mild COPD patients. (17th October 2022) - Armentaro, Giuseppe; Pelaia, Corrado; Cassano, Velia; Miceli, Sofia; Maio, Raffaele; Perticone, Maria; Pastori, Daniele; Pignatelli, Pasquale; Andreozzi, Francesco; Violi, Francesco; Sesti, Giorgio; Sciacqua, Angela
Abstract: Background: Lung hyperinflation and systemic inflammation are currently believed to be the most important causes of right heart alterations in chronic obstructive pulmonary disease (COPD) patients. A multicentre observational study was performed to assess the morphological and functional parameters of right ventricle (RV) in COPD subjects, as well as to evaluate the potential prognostic impact on the development of major cardiovascular adverse events (MACEs). Methods: For this retrospective study, from 1 January 2010 to 31 December 2021, we enrolled COPD patients on the basis of their airflow limitation. In particular, we selected subjects spanning across GOLD 1 and 2 functional stages. Clinical, laboratory and functional parameters were collected at baseline. Echocardiography was routinely performed in all COPD patients. RV dysfunction was defined on the basis of tricuspid annular plane systolic excursion (TAPSE) values. MACE occurrence (non‐fatal ischemic stroke, non‐fatal myocardial infarction, cardiac revascularization or coronary bypass surgery and cardiovascular death) was evaluated during a median follow‐up of 55 (36–72) months. Results: Among the 749 enrolled patients, 408 subjects had a TAPSE value ≥20 mm, while the remaining 341 had a TAPSE value <20 mm. In patients with TAPSE ≥20 mm the observed MACEs were 1.9 events/100 patient‐year, while in the group with a worse right heart function there were 4.2 events/100 patient‐year ( p < .0001). The multivariate analysis model confirmed the association between RV dysfunction and MACE. Indeed, a 1‐mm increase in TAPSE value and the intake of long‐acting β2 ‐receptor agonists (LABA)/long‐acting muscarinic antagonist (LAMA) inhaled therapy were protective factors for the onset of MACE, while the presence of diabetes mellitus and high values of both uric acid (UA) and systolic pulmonary arterial pressure (S‐PAP) enhanced the risk of MACE in study participants. Conclusions: The results of this study showed that in patients with mild COPD there is an association between right heart dysfunction and the risk of MACE during follow‐up. Abstract :